2013
DOI: 10.1016/j.bbmt.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Methylprednisolone for Veno-Occlusive Disease of the Liver in Pediatric Hematopoietic Stem Cell Transplantation Recipients

Abstract: Veno-occlusive disease (VOD) of the liver is a well-recognized serious complication of hematopoietic stem cell transplantation (HSCT), with few successful treatment modalities available for severe disease. Some reports have demonstrated success in adults with the use of high-dose steroid therapy, but experience in the pediatric population is lacking. We retrospectively reviewed HSCT patients treated at our institution since 2003 and identified 15 (2.4%) who developed VOD. Of these, nine (60%) were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 16 publications
2
42
0
1
Order By: Relevance
“…84,85 The overall incidence of VOD/SOS in patients undergoing HSCT was estimated to be 13.7% (range, 0%-62%) in a pooled analysis of 135 studies. 77 In a single-institution study, the reported incidence was 11.5% (Baltimore criteria) and 13.8% (modified Seattle criteria) 75 ; MOD/MOF occurred in ;36% of patients with VOD/SOS diagnosed by Baltimore criteria and 22% by modified Seattle criteria.…”
Section: Key Development Milestones and Approvals Grantedmentioning
confidence: 99%
“…84,85 The overall incidence of VOD/SOS in patients undergoing HSCT was estimated to be 13.7% (range, 0%-62%) in a pooled analysis of 135 studies. 77 In a single-institution study, the reported incidence was 11.5% (Baltimore criteria) and 13.8% (modified Seattle criteria) 75 ; MOD/MOF occurred in ;36% of patients with VOD/SOS diagnosed by Baltimore criteria and 22% by modified Seattle criteria.…”
Section: Key Development Milestones and Approvals Grantedmentioning
confidence: 99%
“…61 A recent pediatric retrospective study described by Myers et al, 2013, 9 patients who received methylprednisolone. 125 Eight of these patients had multi-organ failure secondary to SOS. Response was defined as a 50% reduction in bilirubin level by 10 days after the commencement of therapy.…”
Section: Methylprednisolonementioning
confidence: 99%
“…Overall survival was 78%. 125 Methylprednisolone may be considered for the use in the treatment of SOS with the appropriate caveats of caution regarding infection.…”
Section: Methylprednisolonementioning
confidence: 99%
“…The joint BCSH/BSBMT guideline does not recommend use of tPA for treatment of VOD/SOS due to the associated risk of bleeding [21]; guidelines from the European School of Haematology (ESH)-EBMT note that while tPA may be effective in some patients, it is contraindicated in those with MOF, hemorrhage or severe hypertension [33]. In two clinical studies in patients with VOD/SOS, administration of IV high-dose methylprednisolone (500 mg/m 2 or kg every 12 h) achieved response in the majority of patients, with overall Day +100 survival rates of 58% [41] and 78% [42]. Overall, given the associated risk of infection and limited evidence of its efficacy, this treatment option (used with commensurate caution) may be most appropriate for patients lacking therapeutic alternatives [32].…”
Section: Overview Of Vod/sos Therapiesmentioning
confidence: 99%